FACILITATION OF VIRTUAL MEETINGS ON FINANCIAL AND ECONOMIC ISSUES - Lakhtionova, Liudmyla; Lazareva, Halyna; Yaryna, Alina; Borozenets, Karina (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The essence of facilitation, its types and the secret of preparation for virtual collection are considered. The organizational issues of holding a facilitation session on financial and economic issues are revealed on the example of professional terminology. Proposals for the preparation of the discussion and improvement of its quality were made, which will help to reach consensus by the participants of the virtual meeting.